The Impact of the Tourism Industry on Employment Absorption in Indonesia: A Literature Review - Listiyana Listiyana; Serkan Dilek; Douglas Chiguvi; Mlamli Diko (Indonesian Development Economics and Localities, 2025)
This literature review explores the impact of the tourism sector on employment absorption in various Indonesian regions. By synthesizing findings from multiple studies, we investigate how sub-sectors such as hotels, restaurants, tourist attractions, and travel agencies contribute to job creation. The analysis reveals that while there is generally a positive relationship between tourism activities and employment, the significance and nature of this impact vary across different regions and contexts. Notably, the studies highlight discrepancies in the effects of tourism investments and tourist numbers, indicating the presence of unique regional factors influencing employment outcomes. The findings underscore the need for more region-specific and longitudinal research to understand the nuanced effects of the tourism sector on local labor markets. This review also emphasizes the importance of considering qualitative aspects, such as job quality and economic impact, in future studies to provide a comprehensive understanding of the sector's contribution to employment.